Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(x^{12}-3x^6+1\)
\(=x^{12}-2x^6+1-x^6\)
\(=\left(x^6-1\right)^2-\left(x^3\right)^2\)
\(=\left(x^6-1-x^3\right)\left(x^6-1+x^3\right)\)
\(x^{12}-3x^6+1=\left(x^{12}+x^9-x^6\right)-\left(x^9-x^3+x^6\right)-\left(x^3-1+x^6\right)=x^6\left(x^6+x^3-1\right)-x^3\left(x^6+x^3-1\right)-\left(x^6+x^3-1\right)\)
\(=\left(x^6+x^3-1\right)\left(x^6-x^3-1\right)\)
\(4\left(x+5\right)\left(x+6\right)\left(x+10\right)\left(x+12\right)-3x^2\)
\(=4\left[\left(x+5\right)\left(x+12\right)\right]\left[\left(x+6\right)\left(x+10\right)\right]-3x^2\)
\(=4\left(x^2+17x+60\right)\left(x^2+16x+60\right)-3x^2\)
\(=\left(2x^2+34x+120\right)\left(2x^2+32x+60\right)-3x^2\)
\(=\left(2x^2+33x+120\right)^2-x^2-3x^2\)
\(=\left(2x^2+33x+120-2x\right)\left(2x^2+33x+120+2x\right)\)
\(=\left(2x+15\right)\left(x+8\right)\left(2x^2+35x+120\right)\)
x^40+2.x^20+9 = [x^20 +3]^2 - 4x^20 = [x^20+3]^2 -[2x^10]^2 = [x^20-2x^10+3].[x^20+2x^10+3]
x^12+x^6+1 = x^12 + 2x^6 +1 - x^6 = [x^6 +1]^2 -[x^3]^2 = [x^6 -x^3 +1].[x^6+x^3+1]
x^16+x^8+1 =[x^8+1]^2 - [x^4]^2 = [x^8-x^4+1].[x^8+x^4+1]
x^4+x^2+1 = x^4+2x^2+1 - x^2 = [x^2+1]^2-x^2 = [x^2-x+1].[x^2+x+1]
\(4\left(x+5\right)\left(x+12\right)\left(x+6\right)\left(x+10\right)-3x^2\)
\(=2\left(x^2+60+17x\right).2\left(x^2+60+16x\right)-3x^2\)
\(=\left(2x^2+120+33x+x\right)\left(2x^2+120+33x-x\right)-3x^2\)
\(=\left(2x^2+120+33x\right)^2-x^2-3x^2\)
\(=\left(2x^2+120+33x\right)^2-4x^2\)
\(=\left(2x^2+120+33x+2x\right)\left(2x^2+120+33x-2x\right)\)
\(=\left(2x^2+35x+120\right)\left(2x^2+31x+120\right)\)
\(=\left(2x^2+35x+120\right)\left(x+8\right)\left(2x+15\right)\)
\(x^{12}+x^6+1.\)
\(=x^6.x^6+x^6+1\)
\(=x^6.\left(x^6+1\right)+x^0\)
Nguyễn Huệ Lam:bạn này phân tích buồn cười ghê